Cognitive Aging and Tests of Rationality. (2019) - Park, Sanghyuk; Davis-Stober, Clintin P.; Snyder, Hope K.; Messner, William; Regenwetter, Michel
Abstract: We investigated whether older adults are more likely than younger adults to violate a foundational property of rational decision making, the axiom of transitive preference. Our experiment consisted of two groups, older (ages 60-75; 21 participants) and younger (ages 18-30; 20 participants) adults. We used Bayesian model selection to investigate whether individuals were better described via (transitive) weak order-based decision strategies or (possibly intransitive) lexicographic semiorder decision strategies. We found weak evidence for the hypothesis that older adults violate transitivity at a higher rate than younger adults. At the same time, a hierarchical Bayesian analysis suggests that, in this study, the distribution of decision strategies across individuals is similar for both older and younger adults.